Rancang Bangun Aplikasi “SICATAT“ Sistem Pencatatan Barang Habis Pakai Berbasis Web Menggunakan Laravel - Gunawan, Aldi Rizky; Rini, Eka Mistiko; Suwardiyanto, Devit (Jurnal Informatika dan Komputer, 2025)
An educational institution has a unit responsible for managing consumable goods. Currently, this process is still conducted semi-computerized or manually using manual formulas and online spreadsheets. This leads to inefficiencies and inaccuracies in grouping and numbering used and new incoming items. This research aims to address these issues by developing a web-based application called "SICATAT" for managing consumable goods. The application is developed using PHP and the Laravel framework with a MySQL database. The RAD (Rapid Application Development) method is used to analyze and design the procedures and systems for managing consumable goods. The RAD approach emphasizes the development of responsive and fast software through iterative and repetitive user feedback. It is hoped that the resulting application can manage the consumable goods data effectively, including managing the addition of new items and accurately and efficiently submitting consumable goods. Thus, it is expected that this application can improve efficiency, accuracy, and ease in managing consumable goods in educational institutions, making the process more structured and accessible to all relevant parties. This application will also assist in the overall management of consumable goods.